Gender differences in agricultural productivity in India: Empirical analysis using micro-level panel data - Anupama, G.V.; Falk, Thomas; Sen, Mayukh (International Crops Research Institute for the Semi-Arid Tropics, 2023)
Strong evidence exists that women farmers have less access to land, inputs, labor, and information compared to men. Over the discourse of empirical research conducted in the domain of agricultural productivity, agricultural economists have always pondered over the inclusion of gender diversity as a separate dimension to identify the efficacy of gender roles in agricultural decision-making. In this context, for the purpose of empirical analysis, we used the primary survey data Village Dynamics in South Asia panel dataset collected by the ICRISAT in collaboration with IRRI and ICAR institutes. The research questions formulated for this study are: (a) Today, in India, is there a gender gap in agricultural productivity depending on plot ownership, and household decision-making on agricultural activities? (b) Are there differences in male and female labor use between male- and female-owned plots and does this effect productivity? In the current paper, the Blinder–Oaxaca decomposition technique is used. We found that male labor, both family and hired, shows a significant positive effect on crop value in femaleowned plots, as well as male-owned plots. The gender gap in agricultural productivity using the plot ownership as gender indicator could not be found. A higher share of leased-out plots were owned by women and also a higher share of fallow plots were found to be women owned. The most exciting inference from the study is that synergies are produced when men and women work together and are more productive compared to working separately.